SustainED: Sustainability Resources for Educators Website - Hammel, Mary; Clarke, Dru (Kansas State University, 2010)
SustainED: Sustainability Resources for Educators is a new website initiated by the K-State College of Education. Created as a repository for sustainability and environmental education resources, it reinforces the vision of the College of Education to prepare educators to be knowledgeable, ethical, caring decision makers. The focus is on collected resources pertaining to sustainability in education: lesson plans, books, resource links, recycling hints, people who are making a difference, classroom activities, or environmental education programs or events.
Keywords: Environmental education; Sustainability education; Classroom activities; Lesson plans